Promoting student’s habits of mind and cognitive learning outcomes in science education - Eka Ariyati; Herawati Susilo; Hadi Suwono; Fatchur Rohman (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
: Learning must be able to develop knowledge, skills, and mindsets so that the graduates produced have attitudes, abilities and knowledge that are integrated and skilled in life. One way to achieve learning can be done through habits of mind  because the success of learning is strongly influenced by   habits of mind. The purpose of this study is to as certain how habits of mind and cognitive learning outcomes in biology are affected by learning process oriented guided inquiry learning  with blended learning support. A pretest-postest design wih a non-equivalent control group was employed in this study. The trial ran from February to June 2022. Utilizing the habits of mind questionnaire, pupils’ thought patterns were assessed. Essay tests are also used to evaluate the results of cognitive learning. In this study, google form, LMS, and google meet were used for data collection. Statistical Product and Service Solutions software version 23 is used for data analysis and the results of covariance analysis (ANCOVA) showed a p value < 0,005, meaning that POGIL-supported blended learning can empower habits of mind and cognitive learning outcomes in biology learning. There is a substantial difference between the outcomes of the least significant difference and increasing habits of mind and cognitive learning outcomes. As a result, POGIL with moodle support can be used to enhance students’ habits of mind and cognitive learning results in biology classes.